2012
DOI: 10.1074/jbc.m112.366096
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Tryptophans in Primer Synthesis by the DNA Primase of Bacteriophage T7

Abstract: Background:What are the essential roles of five tryptophans in the T7 primase? Results: Replacement of with the structurally similar tyrosine disturbs the conformation of the ZBD and reduces NTP binding and the catalysis step. Conclusion: Trp-42, -97, and -147 contribute to template binding, NTP binding, and the catalysis step. Significance: Trp-42, -97, and -147 play different but essential roles in T7 DNA primase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Previous reports have also revealed that tyrosine/tryptophan substitutions can have significant effects on the function nucleic acid binding proteins 15 16 . In the human DNA repair enzyme alkyl-adenine DNA glycosylase (AAG) tyrosine/tryptophan substitution mutants in the base-binding site maintain the same nucleic acid binding affinity but dramatically affect the rate constants for nucleotide flipping in and out of the active site 15 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous reports have also revealed that tyrosine/tryptophan substitutions can have significant effects on the function nucleic acid binding proteins 15 16 . In the human DNA repair enzyme alkyl-adenine DNA glycosylase (AAG) tyrosine/tryptophan substitution mutants in the base-binding site maintain the same nucleic acid binding affinity but dramatically affect the rate constants for nucleotide flipping in and out of the active site 15 .…”
Section: Discussionmentioning
confidence: 97%
“…Although tryptophan/tyrosine substitution is considered a relatively conservative change 14 , some reports have demonstrated that tryptophan to tyrosine mutations can have large effects on the proteins function 15 16 . In order to determine the effect of tryptophan/tyrosine substitutions of PC4 orthologous proteins, we have determined the crystal structures of the DNA complexes of the PC4 W89Y mutant and MoSub1 and analysed the effect of the W89Y mutation of PC4 on DNA binding affinity.…”
mentioning
confidence: 99%
“…[9] The C-terminal tail of the gp4 helicase interacts with the front basic patch (Fbp) and the TBD basic patch (TBDbp)o ft he DNA polymerase (gp5/trx), whereas the non-tail region of gp4 also interacts with gp5/trx. [11] The gp2.5 ssDNA-binding protein coats ssDNA to remove its secondary structures and also physically interacts with gp5/trx. [11] The gp2.5 ssDNA-binding protein coats ssDNA to remove its secondary structures and also physically interacts with gp5/trx.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10] The primasedomain of gp4 synthesizes RNA primers to initiate lagging-strand DNA synthesis. [11] The gp2.5 ssDNA-binding protein coats ssDNA to remove its secondary structures and also physically interacts with gp5/trx. [12] These protein interactions main-…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also essential to the production of niacin. 7,8 Therefore, the determination of these three molecules is a subject of great importance not only in the eld of biomedical chemistry and neurochemistry but also for diagnostic and pathological research.…”
Section: Introductionmentioning
confidence: 99%